Pendekatan Social Emotional dalam Pembelajaran Pendidikan Agama Islam untuk Meminimalisir Bullying di Sekolah - Rahmat, Rahmat; Nurhidayati, Titin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
Acts of bullying in every level of education (at the elementary, middle school and high school) are currently a national news issue. Victims of bullying can experience severe trauma and the perpetrators of bullying can end up dropping out of school. Finding this latest phenomenon, this research aims to examine the Social Emotional Approach in Islamic Religious Education Learning to minimize bullying at school. With a qualitative approach and in-depth literature review, this research shows that the Social Emotional Approach in Learning Islamic Religious Education can minimize bullying in schools. As for the findings from the results of this research, the Social Emotional Approach in Islamic Religious Education Learning must be implemented by utilizing several learning dimensions, namely, 1) The Social Emotional Approach utilizes Islamic Religious Education material based on five Social Emotional competencies, 2) The Social Emotional Approach is supported by the Group learning method Investigation, and 3) Social Emotional Approach is also strengthened by learning techniques a) Lecture, b) Discussion, and c) Question and answer.